Development of the High-Tech Sector in Central and Eastern Europe - Joanna M. SZAREK (Communications of International Proceedings, 2021)
Changes to the paradigm of management in the global economy resulting from the development of new technologies and artificial intelligence mean there is a need for assessment of the high-tech sector, especially on a regional scale. Recent months, which have been marked by lockdowns right across the globe as a result of the coronavirus pandemic, are also to be associated with a sharp rise in the adaptation of new technologies and artificial intelligence in the everyday life of societies. This study attempts to conduct an assessment of the advancement of the high-tech sector in the Visegrad Group of countries compared to other states of the European Union prior to the start of the global epidemic. The studies conducted show that the Czech Republic is the regional leader in Central and Eastern Europe as far as the high-tech sector is concerned, equalling the German and Swiss economies in this area.
Keywords: Regional Development; Visegrad Group; Knowledge-Based Economy; High-Tech Sector